Exploring educators' professional learning ecologies in a blended learning environment. (29th April 2019) - Ranieri, Maria; Giampaolo, Mario; Bruni, Isabella
Abstract: In recent years the concept of learning ecology has been interpreted in different ways to highlight its potential for learning and professional development. However, there are several aspects that still deserve to be understood such as, eg, the role that the different contexts come to play within a learning ecology. For this purpose, this paper presents and discusses the results of a study exploring the learning ecologies of educators in a blended programme delivered in higher education. The participants in the study were 85 professionals in the field of education aged between 28 and 58 years. The research design adopted here can be defined as a convergent mixed method where both quantitative and qualitative data were collected through an e‐portfolio. The study found that educators in the sample had different postures, of whom some more aware of their professional roles or Self than others. Moreover, different professional identities seemed to be linked to different learning ecologies, where elements like formal or informal education, cultural artefacts, personal experiences, colleagues or work experiences played a different role. Formal education emerged as having a questionable function, while colleagues came up as a crucial resource.